Application of microscope thermography in testing temperature distribution in a semiconductor laser - Rybiński, Janusz; Bednarek, Michał; Wiśniewski, Przemysław; Świetlik, Tomasz (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Microscope thermography with the use of thermovision camera with spatial resolution 8 μm was applied in testing temperature distribution in semiconductor lasers produced on the basis of nitrides. The conducted tests have shown that the microscope thermography has a potential in characterizing microelectronic devices like semiconductor laser diodes and can be considered as a complementary tool in establishing thermal characteristics of these devices.
Optica Applicata, Vol. 40, 2010, nr 3, s. 609-614
Keywords: optyka; microscope thermography; blue lasers; semiconductor lasers